VERBA BERVALENSI SATU, DUA, DAN TIGA PADA BAHASA MAKASAE - Soares, Antonio Constantino (JURNAL PESONA, 2016)
Makasae language which is called BMk is a language that identifies the three majorregencies of Republica Democratica de Timor-Leste RDTL. Nonetheless, the BMkspeakers generally are able to speak two or more local languages included threeforeign languages such as Indonesian, English, and Portuguese, therefore thepotential of extinction is quite large as the young generations on average preferspeaking foreign languages in their every day lives to speaking their own locallaguages. In essence, this study represents a real effort in seeing the phenomenon ofBMk from linguistic point of view. This study was included qualitative descriptivestudy, in which the basic clause construction BMk analyzed by two main categories,such as its intransitive and transitive clauses, in order to map the lingual unit that canfill the predicate or PRED slot. Based on the research, it was found that the basicconstruction of the clause BMk form Subject+Verb (SV) for the zero object clause, andSubject+Object+Verb (SOV) for the object-needed clause. The description of the BMkbasic clause structure was divided into three main parts, namelyintransitive,ekatransitive clause, and ditransitive clause. This study is also expected toinspire some reseachers who are interested in BMk either micro or macro.Keywords: Basic Clause,Pivot Makasae Language, RDTL